Quality of care for the dying across different levels of palliative care development: A population-based cohort study. (December 2018) - Schelin, Maria EC; Sallerfors, Bengt; Rasmussen, Birgit H; Fürst, Carl Johan
Background: There is a lack of knowledge about how the provision and availability of specialized palliative care relates to the quality of dying in hospital and community-based settings. Aim: We aimed to explore the quality of care during last week of life in relation to different levels of palliative care development. Design: We investigated access to palliative care in Southern Sweden, where one region offers palliative care in accordance with European Association for Palliative Care guidelines for capacity, and the other region offers less developed palliative care. Data on approximately 12, 000 deaths during 2015 were collected from the Swedish Register of Palliative Care. The quality of care was investigated by region, and was measured in terms of assessment of oral health and of pain, and end-of-life conversation, companionship at death and artificial nutrition/fluid in the last 24 h. Results: The overall quality of care during last week of life was not consistently better in the region with fully developed palliative care compared with the less developed region. In fact, for patients dying in hospitals and community-based settings, the quality was statistically significantly better in the less developed region. The small proportion of patients who had access to specialized palliative care had superior quality of care during the last week of life as compared to patients in other care settings. Conclusion: The capacity of specialized palliative care does not per se influence the quality of care during the last week of life for patients in other settings.